2011
DOI: 10.1186/1756-3305-4-224
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of transmission-blocking vaccine candidates Pvs25 and Pvs28 in Plasmodium vivax isolates from Yunnan Province, China

Abstract: BackgroundTransmission-blocking vaccines (TBVs) have been considered an important strategy for disrupting the malaria transmission cycle, especially for Plasmodium vivax malaria, which undergoes gametocytogenesis earlier during infection. Pvs25 and Pvs28 are transmission-blocking vaccine candidates for P. vivax malaria. Assessment of genetic diversity of the vaccine candidates will provide necessary information for predicting the performance of vaccines, which will guide us during the development of malaria va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
0
23
2
Order By: Relevance
“…Pvhap2 showed lower genetic diversity (ranging from 0.00018 to 0.00075 for all global isolates analyzed) [26] compared to other sexual stage transmission-blocking antigens reported in P. vivax such as pvs28/25 (π = 0.0034/0.0013, Yunnan Province of China, [43]; π = 0.0041/0.0023, Myanmar, [44]), pvs48/45 (π = 0.00173, global isolates, [45]), and pvs230 (π = 0.00118, global isolates, [46]). This high level of conservation may be a consequence of the essential function of this protein in fertilization.…”
Section: Discussionmentioning
confidence: 84%
“…Pvhap2 showed lower genetic diversity (ranging from 0.00018 to 0.00075 for all global isolates analyzed) [26] compared to other sexual stage transmission-blocking antigens reported in P. vivax such as pvs28/25 (π = 0.0034/0.0013, Yunnan Province of China, [43]; π = 0.0041/0.0023, Myanmar, [44]), pvs48/45 (π = 0.00173, global isolates, [45]), and pvs230 (π = 0.00118, global isolates, [46]). This high level of conservation may be a consequence of the essential function of this protein in fertilization.…”
Section: Discussionmentioning
confidence: 84%
“…As expected, the overall nucleotide diversities of the four TBV candidates, Pvs25 (π = 0.00065), Pvs28 (π = 0.00000), Pvs48/45 (π = 0.00053), and PvWARP (π = 0.00010), were much lower than those of blood stage proteins such as the C-terminal 42 kDa region of the merozoite surface protein-1 (PvMSP-1 42 ; π = 0.01586) [21] and the Duffy binding protein (PvDBP; π = 0.00299) [46], which were determined from the same P. vivax isolates used in this study. Previous studies have suggested that the antigenic variation of Pvs25 is more limited than that of Pvs28 [6,35]; however, in the Korean isolates, the nucleotide diversity of Pvs28 was lower than that of Pvs25, as only a single haplotype of Pvs28 was identified. Polymorphism analyses of several blood stage antigens, including MSP-1, MSP-3α, and DBP, have strongly suggest that the genetic diversity of Korean P. vivax population has rapidly disseminated in recent years [21,27-29].…”
Section: Resultsmentioning
confidence: 96%
“…Dot represent identical amino acid residue compared to Sal I. 1 [This study], 2 [37], 3 [32], 4 [35], 5 [33], 6 [ABG29073], 7 [36], 8 [31], 9 [9], 10 [32], 11 [ABG29072], 12 [31], 13 [34], 14 [32], 15 [32], 16 [32], 17 [32], 18 Signal peptide region. ( B ) Annual distribution of Pvs25 haplotypes during the study period, 1999–2010.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccine candidate PfCP2.9 from China is listed on the WHO malaria vaccine rainbow table. And many antigens such as Pvs25 and Pvs28 were screened and tested for the development of TBV [42]. R&D on immunology/vaccines might be more promising than antimalarial drugs in China, however, continuous governmental support is essential for this time-consuming and costly battle.…”
Section: Discussionmentioning
confidence: 99%